Oral clinical courses of patients with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection: A clinical follow up (a prospective prevalent cohort) study - Gebretsadik, Heron Gezahegn; Akalu, Gedion Mulatu (Orapuh Journal, 2021)
Introduction Contemporary literature has revealed that SARS-CoV-2 causes acute sialadenitis and related symptoms, such as discomfort, pain, swelling, and secretory dysfunction in salivary glands. The secretory dysfunction is due to SARS-CoV-2 infection-induced xerostomia and other associated clinical courses such as sore tongue, mucosal ulcer, and gingivitis in the oral cavity. Furthermore, it has been reported that COVID-19 causes the development of other oral manifestations. Purpose This cohort study was initiated to identify the possible oral clinical manifestations of patients with SARS-CoV-2 infection admitted at Eka General Hospital COVID-19 treatment center in Addis Ababa, Ethiopia. Materials and Methods A prospective clinical follow-up (a prevalent cohort) study was conducted to identify the possible oral manifestations of SARS-CoV-2 infection among patients admitted at the Eka General Hospital COVID-19 treatment center. Patients were followed for an average period of 3.5 weeks. Results The findings of this cohort prevalent study were adjusted around the main objectives of the research. A total of 55 patients (36 males and 19 females) fulfilling the inclusion criteria were included in the cohort. The age of the cohorts ranged from 8 to 90 years. The overall prevalence of oral clinical courses in patients with SARS-CoV-2 was 0.18 (n=10). Oral mucosal lesions, xerostomia, thickening of saliva yielded prevalence data of 0.5 (n=6), 0.42 (n=5), and 0.08 (n=1), respectively. The oral mucosal lesions prevalence finding was further refined into aphthous lesions 0.5 (n=3), candidiasis 0.17 (n=1), geographic tongue 0.17 (n=1), and localized gingivitis 0.17 (n=1). Conclusion The findings of the study suggest the importance of initiating oral health care for patients with COVID-19. Therefore, multidisciplinary healthcare approaches to management should be promoted to assure optimal health outcomes. Accordingly, oral health care should be a substantial part of the multidisciplinary approach.